IN VITRO ANTI-INFLAMMATORY ACTIVITY OF 4-BENZYLPIPERIDINE - V, Jayashree; S, Bagyalakshmi; K, Manjula Devi; Daniel D, Richard (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To study the in vitro anti-inflammatory activity of 4-benzylpiperidine. Methods: This study was conducted to evaluate the in vitro anti-inflammatory activity of 4-benzylpiperidine using in vitro models such as inhibition of albumin denaturation and proteinase inhibitory activity. Results: This study revealed the dose-dependent inhibition of protein denaturation and proteinase inhibitory activity by 4-benzylpiperidine. Conclusion: In the present study, results indicate that the 4-benzylpiperidine possess anti-inflammatory properties. The drug inhibited the heat induced albumin denaturation and proteinase inhibitory activity. It shows dose-dependent significant activity when compared with a standard drug. Hence, this study gives an idea that the 4-benzylpiperidine can be used as a lead compound for designing a potent anti-inflammatory drug which can be used to cure inflammation. Keywords: Anti-inflammatory activity, 4-Benzylpiperidine, Protein denaturation, Proteinase inhibitory activity.